Sharing Water Across Borders: Assessing the Hydro-Diplomacy Process in the Resolution of Indus River Disputes - Sarah Abigail (Universitas Airlangga, 2024)
Hydro-diplomacy addresses the political aspects of transnational water systems that aims to prevent, lessen, and settle disputes over shared water systems through water governance frameworks. The Indo-Pakistan dispute over the Indus River proves the importance of diplomacy in addressing water related issues. Using a qualitative and descriptive-explorative method, this research aims to explore mechanisms of the Indus River dispute resolutions within the framework of the hydro-diplomacy concept. The paper uses secondary data consisting of journal articles, books, and official documents . This research finds that the Indus River dispute resolution mechanism encompasses the key aspects of hydro-diplomacy, which are: 1) the political means through bilateral meetings and the Indus Water Treaty formulation; 2) preventive means through dispute resolution mechanism in the treaty; 3) integrative means towards the involvement of numerous stakeholders; 4) cooperative aspect through IWT agreements; and 5)technical means through data-sharing practices.